Shelf-Life Of Marinated Rabbit Meat - Jayachandra Kamath G (Department of Livestock Products Technology, College of Veterinary and Animal Sciences, 1997)
Six Newzeland White crossbred rabbit were slaughtered and cut into suitable size. Cut - up parts were divided into 4 equal parts. Three marinades were prepared containing either curd, lime or vinegar, besides a control with salt alone. Samples were stored at -60 C and -200 C for 30 days period. Samples were subjected to different parameters like pH on zero day and tyrosine value, TBA number, aerobic plate count and sensory evaluation on zero, 5th, 15th and 30th day of storage. In this study, observed that the treatments had no significant effect on pH, tyrosine value, TBA number, aerobic plate count whereas storage period had significant effect on above parameters. Marination, storage period and temperature had significant effect on organoleptic qualities. The rabbit meat marinated with lime had lowest pH. Tyrosine value and TBA number obtained was lowest on zero day. On storage, the rabbit meat cuts treated with marinade gave higher scores in taste panel study. Treatment with lime juice was more expensive.